Diagnostic Value of Senior Dental Students in Yazd About of Detection the Proximal Caries on Panoramic Radiographs Compared to Detection of Experts in 1394 - E Romoozi; AR Daneshkazemi; N Tavana (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2016)
Introduction: Tooth decay is the most common chronic disease of man in the world and dentists should receive the capability to accurately diagnose of tooth decay during the training courses. In addition to clinical examination, the panoramic view and intraoral radiography is usually used for the caries detection. Therefore, the detection of caries on X-ray images can have a role in treatment planning.